The Legal Dynamics Dual Positions of Batam Mayor as Head of BP Batam - Handayani, Novia; Affandi, Hernadi; Susanto, Mei (Universitas Internasional Batam, 2024)
This article discusses the legal dynamics of the dual position of the Mayor of Batam as the Head of BP Batam. The focus of this research emphasizes the implications arising from the policy of Government Regulation No. 62/2019, which requires one individual to hold two strategic positions at once, namely as Mayor of Batam, who is authorized to manage the autonomous region and as Head of BP Batam who is authorized to manage investment and development of the Batam area into a special economic zone. This study aims to evaluate the implementation of this dual position policy. Using empirical legal research methods through interviews, literature review, and qualitative analysis, the findings indicate benefits such as increased synergy between economic development and public services. It allows for better coordination in managing the interests of the city and the industrial estate. However, this dual management structure risks weakening Batam's regional autonomy status and creating conflicts of interest that may affect the objectivity of decision-making. On the one hand, this policy is considered a practical solution to resolve the leadership dualism that has been occurring. On the other hand, this policy creates consequences and challenges. This study concludes that to optimize the benefits and minimize conflicts, it is necessary to harmonize more transparent regulations, more effective supervision, and the commitment of officials to prioritize the public interest for implementing local Government in Batam City.